The Utilization of Educational Technology to Improve the Bilingual Abilities of Elementary School Children: A Case Study of First and Second Language Interaction - Lovandri Dwanda Putra; Sri Nur Rahmi; Rina Farah (Yayasan Adra Karima Hubbi, 2025)
Background. Educational technology is increasingly being used to support bilingual learning in elementary school children. The interaction between first and second languages in the context of education is still a challenge in formal learning. The use of technology is expected to be able to improve children's bilingual skills without reducing their first language competence. Purpose. This study aims to analyze the effectiveness of educational technology in improving the bilingual ability of elementary school children and understanding the interaction between first and second languages in the learning process. Method. The research method uses a quantitative approach with a pseudo-experimental design. The sample consisted of elementary school students who were divided into control and experimental groups. Results. The results of the study show that the use of educational technology significantly improves children's bilingual skills. Second language scores increased higher than first languages, but without causing a decrease in first language competence. Conclusion. The conclusion of this study confirms that technology can be an effective tool in increasing bilingualism in elementary school children if used in a directed manner and supported by a conducive learning environment.